Possibilities of Harmonizing Legal Education and Moral Upbringing Based on Social Norms in the New Uzbekistan - Abdukhakimovna, Ergasheva Zilola (International Journal of Formal Education, 2025)
The article studies the theoretical aspects of the harmonization of legal education and moral education in New Uzbekistan, the socio-philosophical and legal analysis of the harmonization of legal education and moral education in New Uzbekistan, the socio-educational tasks and prospects of the harmonization of legal education and moral education in New Uzbekistan. The theoretical and methodological foundations of the harmonization of legal education and moral education in New Uzbekistan are also analyzed.